A single-institution phase II trial of radiation, temozolomide, erlotinib, and bevacizumab for initial treatment of glioblastoma. Issue 7 (16th March 2014) - Clarke, Jennifer L.; Molinaro, Annette M.; Phillips, Joanna J.; Butowski, Nicholas A.; Chang, Susan M.; Perry, Arie; Costello, Joseph F.; DeSilva, Ashley A.; Rabbitt, Jane E.; Prados, Michael D.
Abstract: Background: Both the epidermal growth factor receptor and vascular endothelial growth factor pathways are frequently overexpressed in glioblastoma multiforme. This study combined bevacizumab, a vascular endothelial growth factor inhibitor, and erlotinib, an epidermal growth factor receptor inhibitor, with standard radiation and temozolomide (TMZ), with the goal of improving overall survival (OS). Methods: Treatment consisted of fractionated radiotherapy to 60 Gy, with daily TMZ at 75 mg/m 2 /d and erlotinib 150–200 mg/d (or 500–600 mg/d for patients on enzyme-inducing antiepileptic drugs). Bevacizumab was given at 10 mg/kg every 2 weeks, starting ≥4 weeks after surgery. After radiotherapy, adjuvant TMZ was given at 200 mg/m 2 /d × 5d per 28-day cycle, with unchanged erlotinib and bevacizumab doses. Treatment continued until progression or for 12 months. Efficacy was compared against an institutional historical control. A sample of 55 patients was calculated to provide 85% power to detect a hazard ratio of 0.67 for OS. Results: Fifty-nine patients were enrolled for efficacy analysis after a 15-patient safety lead-in. For the efficacy group, median age was 54 years; median KPS was 90. Gross total and subtotal resections were achieved in 33% and 53%, respectively. The most frequent related grade 3/4 adverse effects were lymphopenia, thrombocytopenia, neutropenia, diarrhea, weight loss, and fatigue. One patient died of disseminated aspergillosis. Median OS was 19.8 months (vs 18 mo for HC, P = .33) and median progression-free survival was 13.5 months (vs 8.6 mo for HC, P = .03). Conclusions: The combination of bevacizumab, erlotinib, TMZ, and radiotherapy appears to be well tolerated and improved progression-free survival but did not reach the primary endpoint of improved OS.